Red Cell Distribution Width with Platelet Count Ratio as a Marker of Severity in Acute Biliary Pancreatitis - Khan, Mahlail Hasan; Gul, Uzma Javed; Bajwa, Khurrum Sarfaraz; Kamal, Tariq; Fahim, Sajid Ameer; Muhammad, Uroosa Din (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate and compare red cell distribution width-to-platelet count ratio (RPR) as marker of severity among patients managed for mild and severe acute biliary pancreatitis.Study Design: Cross-sectional study.Place and Duration of Study: Department of General Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Apr 2021 to Mar 2022. Methodology: Patients were diagnosed with mild or severe acute pancreatitis by using the modified Atlanta criteria: (1) Epigastric pain (2) Increased serum lipase levels, and (3) CT imaging findings indicative of acute pancreatitis. Patients with comorbidities including ischemic heart disease, cerebrovascular accidents, or pregnant females were excluded. The clinical severity of illness was assessed by Ranson and Glasgow scores at the time of admission and at 48 hours. Red cell distribution width-to-platelet count ratio (RPR) values were also assessed at the time of admission. Patient mortality was assessed at 7 days post admission and at 30 days after discharge.Results: Out of a total of 45 patients, mean age was estimated at 47.6±12.0 years while 20(44%) cases fulfilled the criteria of severe acute pancreatitis. Mean RPR values were significantly increased among patients with severe clinical illness (p